The care intersubjectivity and the knowledge in the phenomenological Perspective - Sena, Edite Lago da Silva; Reis, Helca Franciolli Teixeira; Carvalho, Patrícia Anjos Lima de; Souza, Viviane dos Santos (Rev Rene, 2011)
This text has as a main objective to report the study experience and the application of Edmund Husserl and Maurice Merleau- Ponty phenomenological approach in the production of knowledge. These philosophers present the knowledge conception as a result of an intentional process that is developed in the intersubjective experience. In this sense, we present a description of some experiences as caregivers and with family caregivers of people in mental distress, highlighting care as an essential entirety of this relationship that is built dynamically in a temporal perspective.